Kepemilikan Saham Publik dan Corporate Social Responsibility terhadap Kinerja Keuangan - Assyiva Maula Titani; Endah Susilowati (IPM2KPE, 2022)
This study aims to analyze the factors that influence the financial performance of basic and chemical industrial companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. This research method is descriptive quantitative. The sample selection technique uses a purposive sampling technique so that a sample of 20 companies is obtained. The data analysis method uses path analysis or path analysis using the SMART-PLS application. The results of the study show that the path coefficient value is indicated by the influence of Financial Performance on variable X, namely Public Share Ownership which is reflected in the ROE of 3.484. In further tests, the results show that the second biggest influence is the influence of Financial Performance on variable Z, namely Corporate Social Responsibility as reflected in the Corporate Social Responsibility Disclosure Index (CSRDI) of 2.455. In further tests, the results show that Corporate Social Responsibility can mediate Financial Performance and Public Share Ownership of 0.912. In conclusion, Public Share Ownership (KSP) has an effect on financial performance and Financial Performance has an effect on Corporate Social Responsibility (CSR). However, Corporate Social Responsibility (CSR) cannot provide a mediating effect on Public Share Ownership (KSP) and financial performance. Keywords: Corporate Social Responsibility (CSR), Public Share Ownership (KSP), Financial Performance